(untitled) (Journal of Patan Academy of Health Sciences, 2020)
Amid this pandemic, which has been spreading like a wildfire globally, Nepal is not an exception to it. With this, we have been hearing the news of global shortage of personal protective equipment (PPE), with growing concern over the safety of medical community and possibility of cross-contamination. Triaging is less researched and reported in COVID-19. It is as important as PPE, a gateway of safety for health care worker. If we have to manage COVID-19, ensuring triage should be among the priority strategies. Patan hospital is among the few hospitals in Nepal where triaging is practiced.